PENGARUH DISIPLIN KERJA, PENGHARGAAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BADUNG - Ni Luh Nonik Dewiyani; Putu Agus Eka Rismawan; Ary Wira Andika (VALUES, 2023)
This study aims to determine the effect of work discipline, appreciation and work environment on employee performance at the Department of Population and Civil Registration of Badung Regency. Independent variables include work discipline, rewards and work environment. The dependent variable includes employee performance. The research population is a civil servant company (PNS). The samples obtained in this study were 54 employees who were determined based on the saturated sampling method. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that work discipline, appreciation and work environment have a positive effect on employee performance at the Office of Population and Civil Registration of Badung Regency.